The theory of mind story books test validity and reabilty for Turkish preschool children - SARI, OKTAY (ELSEVIER SCIENCE BV, 2012)
The goal of the research was to compare proficiencies of the Theory of Mind of the pre-school period children (4-6 ages) displaying normal development and mentally disabled and autistic children at the interval of 4-8 ages. Mentally disabled (n=30) and autistic (n=39) children, who display normal development (n=426), were compared in terms of the Theory of Mind in line with the second goal of research. When examining differences among the averages of the Test of Theory of Mind Stories in research, it was seen that the average score of the group displaying normal development was higher than of the autistic and mentally disabled group to a significant degree and the averages of the mentally disabled group were higher than of the autistic group to a significant extent (p < 0.05). (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Uzunboylu
Keywords: The Theory of Mind; autistic; intellectual disabled; normal development